2019
DOI: 10.1111/1749-4877.12350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insect infestation on rodent‐mediated dispersal of Quercus aliena: results from field and enclosure experiments

Abstract: Rodents influence plant establishment and regeneration by functioning as both seed predators and dispersers. However, these rodent-plant interactions can vary significantly due to various environmental conditions and the activity of other insect seed-predators. Here, we use a combination of both field and enclosure (i.e, individual cage and semi-natural enclosure) experiments, to determine whether rodents can distinguish sound seeds from those infested with insects. We also demonstrate how such responses to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…In this study, a combination of both semi-natural enclosure and field experiments allowed us to quantitatively assess the interactions between seed traits, seed fates and hoarding behavior of rodents (Xiao et al 2008;Zhang et al 2016c;Zhang et al 2019). We found that seeds of Q. variabilis, which had the greatest seed weight, seed coat thickness, crude fat, crude starch, and crude fiber, were more likely to be eaten after removal or hoarded by rodent species, whereas seeds of Q. serrata with lower seed weight, seed coat thickness, crude protein, and crude fiber were harvested and hoarded less frequently but often eaten in situ by rodent species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, a combination of both semi-natural enclosure and field experiments allowed us to quantitatively assess the interactions between seed traits, seed fates and hoarding behavior of rodents (Xiao et al 2008;Zhang et al 2016c;Zhang et al 2019). We found that seeds of Q. variabilis, which had the greatest seed weight, seed coat thickness, crude fat, crude starch, and crude fiber, were more likely to be eaten after removal or hoarded by rodent species, whereas seeds of Q. serrata with lower seed weight, seed coat thickness, crude protein, and crude fiber were harvested and hoarded less frequently but often eaten in situ by rodent species.…”
Section: Discussionmentioning
confidence: 99%
“…2017; Zhang et al . 2019). The animals in reproductive conditions were released immediately in place, and other captured rodents were then transferred with live‐traps to our laboratory for housing, where were routinely measured and recorded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, seed dispersal is a key life‐history stage in plants, during which seeds or diaspores rely on agents such as wind and animals to spread to suitable sites away from the parent plant. Various studies have demonstrated that animals, especially small rodents, play a vital role in seed dispersal and they affect the seed‐to‐seedling period of plant regeneration (Abe et al, 2006 ; Williams‐Linera et al, 2011 ; Yu et al, 2017 , 2018 ; Zhang et al, 2019 , 2020 ). Usually, rodents eat part of the food (plant seeds or fruits) immediately after finding it, and the other part is often left scattered by the trees or stored to obtain food during periods of shortage (Ma et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%